A survey of libraries among selected agencies under the Office of the President with implications toward resource sharing - De Castro, Helen C. (1993)
This study attempts to survey the existing resources, facilities, equipment, services, resource sharing activities and the possibility of establishing a library cooperative system among the agencies under the Office of the President.